Cam küre, CaCO3 ve talk dolgulu polipropilen hibrit kompozitelerin mekanik ve fiziksel özelliklerinin incelenmesi - Kansu, Yasin (My University, 2005)
The main aim of this research was to analyse the effect of inorganic fillers with different structure and contents from each others on the physical, thermal, morphological and mechanical properties for polypropylene. In this research, plate-like shaped talc, spherical shaped CaCO3 and glass bead were used as fillers. Polypropylene and fillers were compounded at 10%, 20%, 30% and 40% (wt/ wt ratios) with a twin-screw extruder. These composites were injection-molded as standart samples with an injection-molding machine and tests were performed. As a result of these experiments, it was found that all of the three fillers have different effects on mechanical and physical properties of the polypropylene. Due to the talc increased mechanical properties of polypropylene more than the other fillers, we could think it is as reinforcement filler. But when the weld line occured, drastic decrease are observed in tensile strength and strain values because of the fact that plate-like shaped talc oriented in existing weld line. On the other hand, it was observed that spherical shaped CaCO3 and glass bead fillers have better tensile strength and strain values than plate-like shaped talc in every filler ratio and in every sample which had weld line. Morever, hybrid composites having the mixture of two fillers, added in polypropylene and tests were performed. Filling ratio for hybrid composites were determined as 40%. Composites prepared in 10%-30%, 20%-20%, 30%-10% (wt/ wt ratios) and tests also were performed. Synergistic effects were observed by with combination two different fillers with advantageous properties. Thanks to the this synergistic effect, some improvements could be observed in mechanical properties of the polypropylene even in in the presence of weld line. As a result of the tests, it is found that hybrid composite which has talc in it has better test results. It is observed that talc/ CaCO3 hybrid filler had reinforcing effect even weld line is present in polypropylene matrix. Bu çalışmanın temel amacı, farklı yapı ve içeriklere sahip inorganik dolgu mad-delerinin polipropilenin fiziksel, ısıl, morfolojik ve mekanik özelliklerine etkilerini incelemektir. Dolgu maddesi olarak plaka şeklindeki talk, küresel şekillerdeki CaCO3 ve cam küre kullanılmıştır. Dolgu maddeleri polipropilen ile ekstruderde ağırlık ola-rak %10, 20, 30 ve 40 oranında karıştırılmışlardır. Hazırlanan karışımlar enjeksiyon kalıplama yöntemiyle standart numuneler halinde basılmış ve testler gerçekleştiril-miştir. Yapılan deneyler sonucunda üç dolgu maddesinin de polipropilenin mekanik ve fiziksel özellikleri üzerinde farklı etkilere neden olduğu belirlenmiştir. Talk dolgusu polipropilenin mekanik özelliklerini diğer dolgu maddelerine göre arttırmasından dolayı güçlendirici dolgu maddesi olarak düşünülebilir. Ancak, birleşme çizgisi var-lığında plaka şeklindeki talkın yönlenmesinden dolayı, akma dayanımı ve yüzde uza-ma değerlerinde önemli düşüşler gözlenmiştir. Küresel şekildeki CaCO3 ve cam küre dolgularının ise tüm dolgu oranlarında birleşme çizgisi içeren numunelerde plaka şeklindeki talka göre çok daha iyi akma dayanımı ve yüzde uzama değerlerine sahip olduğu gözlenmiştir. Ayrıca, dolgu maddelerinin ikili karışımlarından oluşan hibrit bileşikleri de poli-propilene eklenip, testler uygulanmıştır. Hibrit bileşikler için dolgu oranı ağırlıkça %40 olarak belirlenmiştir. %10-30, %20-20 ve %30-10 olacak şekilde karışımlar hazırlanmış ve testler gerçekleştirilmiştir. İki farklı dolgu maddesinin avantajlarının birleşmesi ile sinerjik bir etki oluşmuş ve oluşan bu sinerjik etki ile özellikle birleşme çizgisi olması durumunda polimerin mekanik özelliklerinde iyileşmeler meydana gelmiştir. Testler sonucunda, talk içeren hibrit karışımların daha iyi değerlere sahip olduğu bulunmuştur. Talk/ CaCO3 hibrit dolgusunun birleşme çizgisi varlığında bile polipropilen matrisi güçlendirici özelliği olduğu tespit edilmiştir. Hazi
Keywords: Kimya mühendisliği ve ilgili konular; Kimya, Organik; Organik kimyasallar; Polimerler ve Polimerleşme; Sanayi kimyasalları teknolojisi